2017
DOI: 10.4269/ajtmh.16-0727
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis E Among Boston Area Travelers, 2009–2010

Abstract: Abstract. We determined the prevalence of IgG antibodies to hepatitis E virus (anti-HEV IgG) among travelers attending Boston-area travel health clinics from 2009 to 2010. Pre-travel samples were available for 1,356 travelers, with paired pre-and post-travel samples for 450 (33%). Eighty of 1,356 (6%) pre-travel samples were positive for anti-HEV IgG. Compared with participants who had never lived in nor traveled to a highly endemic country, the pre-travel prevalence odds ratio (POR) of anti-HEV IgG among part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…The pretravel seroprevalence of 15% we found was higher than the 2% found in the study of travelers from the Netherlands conducted during 2006–2007 ( 8 ) and the 6% found in the study of Boston, Massachusetts, USA, area travelers conducted during 2009–2010 ( 15 ). However, seroprevalence in this study was lower than the 27% found in the study of blood donors from the Netherlands conducted during 2011 ( 16 ) and in the population of Amsterdam during 2004 ( 17 ).…”
Section: Discussioncontrasting
confidence: 80%
“…The pretravel seroprevalence of 15% we found was higher than the 2% found in the study of travelers from the Netherlands conducted during 2006–2007 ( 8 ) and the 6% found in the study of Boston, Massachusetts, USA, area travelers conducted during 2009–2010 ( 15 ). However, seroprevalence in this study was lower than the 27% found in the study of blood donors from the Netherlands conducted during 2011 ( 16 ) and in the population of Amsterdam during 2004 ( 17 ).…”
Section: Discussioncontrasting
confidence: 80%
“…There is also considerable local variation in antibody prevalence, with the general population in the Mid-Western States tending to have the highest prevalence, possibly due to increased exposure to swine in those areas [8]. However, many studies examining risks for HEV infection at the local, rather than national level, focus on high risk populations (ie: swine veterinarians, acute liver failure patients, or travelers) or blood donors (adults only) rather than members of the general population [9][10][11].…”
Section: Introductionmentioning
confidence: 99%